SAVI Learning Model and Its Effect on Students’ Interest in Islamic Religious and Character Education - Nabila, Rifa Jihan; Anwar, Chairul; Romlah, Listiyani Siti (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2025)
Learning interest is a crucial factor determining the effectiveness of the learning process, including in Islamic Religious Education (PAI) and Character Building. This study examined the effect of the SAVI learning model on students' learning interest, particularly in terms of student engagement, at SMP Negeri 1 Waway Karya. This study employed a quantitative approach with a quasi-experimental post-test-only control group design. The sample consisted of two seventh-grade classes, selected through simple random sampling: the experimental class, which used the SAVI learning model, and the control class, which used teacher-centered learning methods. The research instrument was a non-test questionnaire that measured student engagement in learning. The results of normality and homogeneity tests indicated that the data were normally distributed and had homogeneous variance. The Independent Samples t-test yielded a Sig. (2-tailed) value of 0.037 (<0.05), indicating a significant difference between the experimental and control groups. The average learning interest in the experimental group was 75.4, while that in the control group was 68.1, with standard deviations of 5.8 and 7.2, respectively. Cohen's d value for the effect size was 0.548, indicating a moderate effect. These findings demonstrate that the SAVI learning model has a significant and positive impact on increasing students' interest in learning. Therefore, this study confirms that the application of the SAVI model is feasible in Islamic Religious Education and Character Education, encouraging student engagement and enthusiasm.